Evaluation of physical-mechanical properties of self-adhesive versus conventional resin cements - Maria Helena Rossy Borges; Carmen Gilda Tavares Dias; Cristiane de Melo Alencar; Cecy Martins Silva; Renata Antunes Esteves (Universidade Estadual de Campinas, 2020)
Aim: The purpose of this study was to compare the microhardness, diametral tensile strength, compressive strength and the rheological properties of self-adhesive versus conventional resin cements. Methods: Specimens of a conventional (RelyX ARC) and 3 self-adhesive (RelyX U200, Maxcem Elite, Bifix SE) types of resin cements were prepared. The Knoop test was used to assess the microhardness, using a Microhardness Tester FM 700. For the diametral tensile strength test, a tensile strength was applied at a speed of 0.6 mm/minute. A universal testing machine was used for the analysis of compressive strength and a thermo-controlled oscillating rheometer was used for the Rheology test. One-way ANOVA and Tukey's test (α=0.05) were used for data analysis. Results: According to microhardness analysis, all the cements were statistically similar (p>0.05), except for Maxcem that presented lower hardness compared with the other cements in relation to the top surface (p<0.05). In the diametral tensile strength test, Relyx U200 and RelyX ARC cements were statistically similar (p>0.05), presented higher value when compared to the Maxcem and Bifix cements (p<0.05). The compressive strength of RelyX ARC and Maxcem Elite cements was statistically higher than RelyX U200 and Bifix cements (p<0.05). Regarding the rheology test, Maxcem Elite and RelyX ARC cements showed a high modulus of elasticity. Conclusions: The self-adhesive cements presented poorer mechanical properties than conventional resin cement. Chemical structure and types of monomers employed interfere directly in the mechanical properties of resin cements.